The Effectiveness of Team Games Tournament with Edmodo on Students’ Learning Outcome and as an Attempt to Support the Pillar of Paperless Conservation - Rizaki, Ibnu; Peniati, Endah; Purwantoyo, Eling (Journal of Biology Education, 2019)
Model and learning media is the important component that can affect the result of learning outcomes. The appropriate model of learning can improve students learning activity. The result of interest questionnaire and interview with biology teachers in SMA N 1 Jatibarang showed that student activity interest at medium category and paper became the main option for all administration and documentation needs. Team Games Tournament with edmodo was rated as the most appropriate model that match the situations and conditions in SMA N 1 Jatibarang nowadays. This model has high efficacy level to solve the activity and learning outcome problem, meanwhile Edmodo is the proper rated class-based website as the solution for paperless attempt. This study aim is to evaluate the effectiveness of Team Games Tournament with edmodo toward student learning outcome and as an attempt to support the pillar of paperless conservation in SMA N 1 Jatibarang. A pre-experimental, One Group Pretest-Posttest Design was used. Samples was collected by purposive sampling methods. All XI MIPA students used as experiment class. Data collection method in this study is a test and questionnaire based methods. Data analysis result showed that classical mastery at 93.26% and N-gain score at 0.70 with high category. The student opinion towards TGT method with edmodo has a very good category. The conclusion is Team Games Tournament model with edmodo effective towards student learning outcome and as an attempt to support the pillar of paperless conservation.